Analysis of the Types of Epidemiology Diseases and Incidence Level in The Population - Xodjiyeva Gulirano Sayfullayevna; Kamalov Shahzodbek Usman ugli (Zien Journals, 2024)
In this article, types of infectious diseases, allergies, nervous system, microorganisms, incidence rate
Keywords: infectious diseases; allergy; nervous system; microorganisms